2018
DOI: 10.1021/acs.chemmater.8b01771
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Outstanding Oxygen Mass Transport Properties of Mn-Rich Perovskites in Grain Boundary-Dominated La0.8Sr0.2(Mn1–xCox)0.85O3±δ Nanostructures

Abstract: Ion transport in solid-state devices is of great interest for current and future energy and information technologies. A superior enhancement of several orders of magnitude of the oxygen diffusivity has been recently reported for grain boundaries in lanthanum–strontium manganites. However, the significance and extent of this unique phenomenon are not yet established. Here, we fabricate a thin film continuous composition map of the La0.8Sr0.2(Mn1–xCox)0.85O3±δ family revealing a substantial enhancement of the gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 56 publications
(130 reference statements)
4
49
0
Order By: Relevance
“…Regarding the surface exchange (Figure e), an analogous trend to the oxygen diffusion is observed in the Mn deficient GBs. The strong coupling of the two oxygen parameters, along with the observed oxygen depletion in the GBs, corroborate the hypothesis that the accumulation of oxygen vacancies is at the origin of the large improvement of the oxygen reduction reactions reported for manganite thin films by different authors . This conclusion is also supported by theoretical works from Choi et al and Mastrikov et al, where the scarce concentration of oxygen vacancies was found as the limiting factor for oxygen incorporation in bulk LSM.…”
Section: Formation Energy Of Lamn× Defect Calculated By Dft In Differsupporting
confidence: 87%
See 1 more Smart Citation
“…Regarding the surface exchange (Figure e), an analogous trend to the oxygen diffusion is observed in the Mn deficient GBs. The strong coupling of the two oxygen parameters, along with the observed oxygen depletion in the GBs, corroborate the hypothesis that the accumulation of oxygen vacancies is at the origin of the large improvement of the oxygen reduction reactions reported for manganite thin films by different authors . This conclusion is also supported by theoretical works from Choi et al and Mastrikov et al, where the scarce concentration of oxygen vacancies was found as the limiting factor for oxygen incorporation in bulk LSM.…”
Section: Formation Energy Of Lamn× Defect Calculated By Dft In Differsupporting
confidence: 87%
“…It was recently discovered that GBs in La 0.8 Sr 0.2 MnO 3± δ (LSM) thin films are responsible for a substantial enhancement of oxygen diffusion and oxygen reduction reactions (ORR), contrary to what is determined in many oxides where the GBs are known to hinder the oxygen mobility . The improvement of oxygen mass transport properties is able to completely change the nature of the material converting the mainly electronic LSM into a good mixed ionic–electronic conductor (MIEC).…”
Section: Formation Energy Of Lamn× Defect Calculated By Dft In Differmentioning
confidence: 99%
“…Therefore, solid electrolytes need to have high ionic conductivity with negligible electronic conductivity. [17][18][19] Although SOFCs have so many advantages and broad application prospects, they have not been widely commercialized due to their high operating temperatures (>750°C), which is mainly determined by the oxide ion conductivity of the electrolytes. Such high operating temperatures lead to a series of issues, such as expensive fuel-cell components, higher plant cost, slow start up and shut down, poor cycling capability, and poor durability arising from thermal and chemical compatibility between the components.…”
Section: Xiaohui LImentioning
confidence: 99%
“…Special attention has been put on the enhanced mixed ionic-electronic properties of strontium-doped lanthanum manganites (LSM). [27,[86][87][88] Two independent studies by Saranya et al [27,88] and Navickas et al [86] reported fast oxygen conduction properties through grain boundaries of LSM. In both works, it was shown how grain boundaries improve the mixed ionic electronic character of a mainly electronic conductor such as LSM, thus opening up the possibility for LSM to be employed as an electrode for solid oxide fuel cell (SOFC) systems.…”
Section: Homointerfaces: Grain Boundary-dominated Materialsmentioning
confidence: 99%